Genetic diversity of Plasmodium vivax in Kolkata, India - Day Nick PJ; Addy Manjulika; Maji Ardhendu; Tonomsing Naowarat; Nontprasert Apichart; Chotivanich Kesinee; Nandy Amitabha; Imwong Mallika; Kim Jung-Ryong; White Nicholas J; Pukrittayakamee Sasithon (Malaria Journal, 2006)
Abstract Background Plasmodium vivax malaria accounts for approximately 60% of malaria cases in Kolkata, India. There has been limited information on the genotypic polymorphism of P. vivax in this malaria endemic area. Three highly polymorphic and single copy genes were selected for a study of genetic diversity in Kolkata strains. Methods Blood from 151 patients with P. vivax infection diagnosed in Kolkata between April 2003 and September 2004 was genotyped at three polymorphic loci: the P. vivax circumsporozoite protein ( pvcs ), the merozoite surface protein 1 ( pvmsp 1) and the merozoite surface protein 3-alpha ( pvmsp 3-alpha). Results Analysis of these three genetic markers revealed that P. vivax populations in Kolkata are highly diverse. A large number of distinguishable alleles were found from three genetic markers: 11 for pvcs , 35 for pvmsp 1 and 37 for pvmsp 3-alpha. These were, in general, randomly distributed amongst the isolates. Among the 151 isolates, 142 unique genotypes were detected the commonest genotype at a frequency of less than 2% (3/151). The overall rate of mixed genotype infections was 10.6%. Conclusion These results indicate that the P. vivax parasite population is highly diverse in Kolkata, despite the low level of transmission. The genotyping protocols used in this study may be useful for differentiating re-infection from relapse and recrudescence in studies assessing of malarial drug efficacy in vivax malaria.